Accommodating linguistic prejudice? Examining English teachers' language ideologies. Issue 1 (8th April 2019) - Metz, Mike
Abstract : Purpose: The purpose of this study is to support the integration of scientifically grounded linguistic knowledge into language teaching in English Language Arts (ELA) classrooms through building an understanding of what teachers currently know and believe about language. Design/methodology/approach: In total, 310 high school English teachers in the USA responded to a survey about their language beliefs. Statistical analysis of responses identified four distinct constructs within their belief systems. Sub-scales were created for each construct, and hierarchical regressions helped identify key characteristics that predicted beliefs along a continuum from traditional/hegemonic to linguistically informed/counter-hegemonic. Findings: Key findings include the identification of four belief constructs: beliefs about how language reveals speaker characteristics, beliefs about how society perceives language use, beliefs about how language should be treated in schools and beliefs about the English teacher's role in addressing language use. In general, teachers expressed counter-hegemonic beliefs for their own role and their view of speaker characteristics. They expressed hegemonic beliefs for societal perceptions and the dominant school language narrative. Taking a linguistics class was associated with counter-hegemonic beliefs, and teaching longer was associated with more hegemonic beliefs. Practical implications: The findings of this study suggest that the longer teachers teach within a system that promotes hegemonic language practices, the more they will align their own beliefs with those practices, despite having learned linguistic facts that contradict pervasive societal beliefs about language. The Dominant School Language Narrative currently accommodates, rather that disrupting, linguistic prejudice. Originality/value: A current understanding of teachers' language ideologies is a key step in designing teacher professional development to help align teaching practices with established linguistic knowledge and to break down a socially constructed linguistic hierarchy based on subjective, and frequently prejudicial, beliefs.